The campaign - Roach, Jay 1957- (Warner Home Video, 2013)
Jay Roach directs this political comedy starring Will Ferrell and Zach Galifianakis. The film follows two rival politicians from the American South as they vie to win an election to represent their small North Carolina congressional district in the US House of Representatives. When congressman Cam Brady (Ferrell) becomes embroiled in a public scandal, aspirational Beltway outsider Marty Huggins (Galifianakis) seizes the opportunity to mount his challenge
Orig.: USA 2012